An Need of Analyze for Developing Interactive Multimedia Based on Local Wisdom in The Teaching of "Senjang" as Part of Cultural Arts Education in Elementary Schools - Khusnul Khotimah; Makmum Raharjo; Farhan Yadi (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2006)
This research aims to analyze the need for developing interactive multimedia based on local wisdom in the teaching of Senjang within Cultural Arts education at the elementary school level. The novelty of this study lies in its specific focus on Senjang as a form of local oral literature that has received limited attention in the development of elementary school learning media, positioning it as both cultural heritage and an instructional resource. The research was motivated by students’ low understanding of local cultural arts content, declining interest in Senjang, and the absence of adequate and engaging instructional media. A descriptive quantitative approach was employed, with data collected through questionnaires administered to 32 participants consisting of 30 students and 2 teachers. The results indicate a strong demand for interactive multimedia learning media, with students reporting increased interest, understanding, and engagement, while teachers found such media helpful in delivering the material. The needs analysis showed that students’ needs reached 96.8 percent, teachers’ needs 98.33 percent, and media needs 93.33 percent, all categorized as highly needed. These findings emphasize the importance of developing interactive, culturally rooted learning media to support the preservation of Senjang as local oral literature and to improve the quality of cultural arts education in elementary schools